Phase III (and maybe IV) of the SIMPLE dark matter search experiment at the LSBB - Girard T.A.; Ramos A.R.; Roche I.L.; Fernandes A.C. (E3S Web of Conferences, 2014)
with the recent conclusion of Phase II, SIMPLE has ended its use of Superheated Droplet Detectors (SDD) in the WIMP search effort. An in-progress Phase III comprises a transition to larger mass bubble chamber technology, using many of the lessons gained from the previous phase since the underlying physics is identical. We describe the progress of the activities, to include several ∼1 kg prototype chambers, each 4× the total Phase II active mass, which are undergoing testing, prior to a rescaling to a 50 kg capacity within a Phase IV modular 1 ton detector for a definitive astroparticle search effort.